Magnolol Attenuates Right Ventricular Hypertrophy and Fibrosis in Hypoxia-Induced Pulmonary Arterial Hypertensive Rats Through Inhibition of the JAK2/STAT3 Signaling Pathway - Fu, Minyi; Luo, Fangmei; Wang, Eli; Jiang, Yueping; Liu, Shao; Peng, Jun; Liu, Bin (Frontiers in Pharmacology, 2021)
Right ventricular (RV) remodeling is one of the essential pathological features in pulmonary arterial hypertension (PAH). RV hypertrophy or fibrosis are the leading causes of RV remodeling. Magnolol (6, 6', 7, 12-tetramethoxy-2,2’-dimethyl-1-β-berbaman, C18H18O2) is a compound isolated from Magnolia Officinalis. It possesses multiple pharmacological activities, such as anti-oxidation and anti-inflammation. This study aims to evaluate the effects and underlying mechanisms of magnolol on RV remodeling in hypoxia-induced PAH. In vivo, male Sprague Daley rats were exposed to 10% O2 for 4 weeks to establish an RV remodeling model, which showed hypertrophic and fibrotic features (increases of Fulton index, cellular size, hypertrophic and fibrotic marker expression), accompanied by an elevation in phosphorylation levels of JAK2 and STAT3; these changes were attenuated by treating with magnolol. In vitro, the cultured H9c2 cells or cardiac fibroblasts were exposed to 3% O2 for 48 h to induce hypertrophy or fibrosis, which showed hypertrophic (increases in cellular size as well as the expression of ANP and BNP) or fibrotic features (increases in the expression of collagen Ⅰ, collagen Ⅲ, and α-SMA). Administration of magnolol and TG-101348 or JSI-124 (both JAK2 selective inhibitors) could prevent myocardial hypertrophy and fibrosis, accompanied by the decrease in the phosphorylation level of JAK2 and STAT3. Based on these observations, we conclude that magnolol can attenuate RV hypertrophy and fibrosis in hypoxia-induced PAH rats through a mechanism involving inhibition of the JAK2/STAT3 signaling pathway. Magnolol may possess the potential clinical value for PAH therapy.